filmov
tv
Conversion of propositional logic sentence to conjunctive normal form (PL to CNF) - example 3
Показать описание
This video is a part of series on Propositional Logic.
Example:
(A?B:(C → D)) ≡ (if A then B else (C implies D))
To see the layout of the series, follow the link bellow:
I Had a Crack at it is a personal blog that contains notes on Maths, Electronics and Informatics.
Example:
(A?B:(C → D)) ≡ (if A then B else (C implies D))
To see the layout of the series, follow the link bellow:
I Had a Crack at it is a personal blog that contains notes on Maths, Electronics and Informatics.